Effects of Islamic Caring Mindfulness-Based Program on Spiritual Well-Being and Fatigue in Indonesian Women with Advanced Breast Cancer Undergoing Chemotherapy: A Randomized Controlled Trial - Maria Komariah (Prince of Songkla University, 2024)
Master of Nursing (Nursing (International Program)), 2019